Oil Accumulation in Transgenic Potato Tubers Alters Starch Quality and Nutritional Profile - Mitchell, Madeline; Pritchard, Jenifer; Okada, Shoko; Larroque, Oscar; Yulia, Dina; Pettolino, Filomena; Szydlowski, Nicolas; Singh, Surinder; Liu, Qing; Ral, Jean-Philippe (Frontiers in Plant Science, 2017)
Plant storage compounds such as starch and lipids are important for human and animal nutrition as well as industry. There is interest in diverting some of the carbon stored in starch-rich organs (leaves, tubers and cereal grains) into lipids in order to improve the energy density or nutritional properties of crops as well as providing new sources of feedstocks for food and manufacturing. Previously, we generated transgenic potato plants that accumulate up to 3.3 % triacylglycerol (TAG) by dry weight in the tubers, which also led to changes in starch content, starch granule morphology and soluble sugar content. The aim of this study was to investigate how TAG accumulation affects the nutritional and processing properties of high oil potatoes with a particular focus on starch structure, physical and chemical properties. Overall, TAG accumulation was correlated with increased energy density, total nitrogen, amino acids, organic acids and inorganic phosphate, which could be of potential nutritional benefit. However, TAG accumulation had negative effects on starch quality as well as quantity. Starch from high oil potatoes had lower amylose and phosphate content, reduced peak viscosity and higher gelatinization temperature. Interestingly, starch pasting properties were disproportionately affected in lines accumulating the highest levels of TAG (> 2.5 %) compared to those accumulating only moderate levels (0.2-1.6 %). These results indicate that optimised engineering of specialised crops for food, feed, fuel and chemical industries requires careful selection of traits, and an appropriate level of transgene expression, as well as a better understanding of starch structure and carbon partitioning in plant storage organs.